Shaping forest safety nets with markets: adaptation to climate change under changing roles of tropical forests in Congo Basin - Nkem, J.; Kalame, F.B.; Idinoba, M.; Somorin, O.A.; Ndoye, O.; Awono, A. (2010)
Tropical forests hold several goods and services used by forest-dependent people as safety nets to traverse difficult periods of resource supply. These same goods and services are constantly surrounded by emerging markets linking remote communities with major urban centers nationally and internationally. How these markets affect adaptation remains unclear. This paper examines the roles of markets in non-timber forest products that normally serve as safety nets for forest communities, and the implications for climate change adaptation in the Congo Basin. Following the identification and prioritization of forest-based development sectors for adaptation by stakeholders, the types of markets and trades surrounding the identified sectors were examined in two provinces in the Democratic Republic of Congo as a case study in order to evaluate revenue flows and their potential contribution to adaptation by local communities. The distribution of the market revenue leaves local people with returns much lower than the worth of the commodity, while wholesalers and retailers reap most of the benefits and profit from the high variability in volume and market earnings for the same commodity across provinces. Markets may increase the value of a commodity as observed in this study, but their contributions to adaptation appear highly limited for local communities following their distribution among the stakeholders in the market chain. This is likely to be worse in free market settings, especially when it diminishes the safety net roles of forest goods and services. Markets should therefore complement rather than substitute forests roles for adaptation to climate change in tropical forest countries. Capturing the benefits of trade for adaptation is crucial but will require policy reforms and further research that addresses the complexity in benefit sharing.